2017
DOI: 10.35613/ccl.2017.1073
|View full text |Cite
|
Sign up to set email alerts
|

What women want—And why you want women—In the workplace

Abstract: This study of women and men leaders highlights new findings on what women want in the workplace and why organizations should want women. Key findings on why organizations should want women: • Participants from organizations with a higher percentage of women rated their organizations more favorably on 7 items related to job satisfaction, organizational dedication, burnout, and employee engagement. • Participants with female bosses felt more supported (especially female participants) and experienced less job-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 6 publications
1
13
0
3
Order By: Relevance
“…For instance, a 2014 Gallup Study (Badal, 2014) found that among over 800 business units in two different industries, gender diverse groups had better financial outcomes compared to groups dominated by one gender. A study by the Center for Creative Leadership, found that people who worked in organizations with a higher percentage of women felt more job satisfaction and organizational dedication and less work-related burnout (Clerkin, 2017).…”
Section: Elevating Womens Leadership In India: Issues and Insightsmentioning
confidence: 99%
“…For instance, a 2014 Gallup Study (Badal, 2014) found that among over 800 business units in two different industries, gender diverse groups had better financial outcomes compared to groups dominated by one gender. A study by the Center for Creative Leadership, found that people who worked in organizations with a higher percentage of women felt more job satisfaction and organizational dedication and less work-related burnout (Clerkin, 2017).…”
Section: Elevating Womens Leadership In India: Issues and Insightsmentioning
confidence: 99%
“…Women may also experience more rewarding work relations in female-dominated employment environments. Women tend to be more satisfied in women-dominated work contexts (Fricke & Beehr, 1992;Smart & Ethington, 1987) and rate their organizations higher under these conditions (Clerkin, 2017) whereas they are less satisfied in male-dominated workplaces, perhaps because they have higher expectations in these environments (Clark, 1997;Sloane & Williams, 2000).…”
Section: Work Relationsmentioning
confidence: 99%
“…As well as being the ‘right thing to do’, the aforementioned Nordic model has been shown to have contributed considerably to economic growth, re-emphasizing the societal loss from inequity. Work by the Center for Creative Leadership (CCL), the primary community of leading and emerging women entrepreneurs and executives in Silicon Valley, 10 has shown that greater senior female leadership improves perceived line management support, employee engagement and organisational dedication, whilst reducing staff burnout.…”
Section: Next Steps: the Right Thing Is The Best Thing – Unleashing Tmentioning
confidence: 99%